(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The main goal of the country’s tax system is the implementation of a fiscal function, which is to collect taxes. This helps effective tax administration. It also ensures the implementation of the stimulating function aimed at more efficient use of labor, material resources of the organization. Within the framework of this study, the author examines existing problems in the field of tax security and developed measures to overcome them. The practical significance of the work lies in the fact that the results obtained during the study can be applied to solve existing problems.